1984
DOI: 10.1159/000123860
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chromatography of Hypothalamic Corticotrophin-Releasing Factors

Abstract: Extracts of rat stalk-median eminences were chromatographed on Sephadex G-50 and BioGel P2. Effluent fractions were monitored for corticotrophin-releasing factor (CRF) bioactivity, using the perfused isolated pituitary cell column bioassay, and radioimmunoassay for CRF-41, AVP, oxytocin, neurophysin, adrenocorticotrophic hormone (ACTH) and luteinizing hormone-releasing hormone (LHRH). Porcine hypothalami were also chromatographed on Sephadex G-50. Our results suggest that vasopressin and a peptide in the rat r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In conclusion, we have demonstrated a development of CRF, AVP and SRIF production by neurons over extended periods in culture as assessed by their peptide content and increasing responses to depolarizing stimuli. Such a system should prove useful in the study of the effects of environmental factors such as steroids, peptides and neurotransmitters on the maturation of peptidergic neurons and the synthesis and release of CRF, AVP and SRIF.Past work on the nature of corticotropin-releasing factor (CRF) in hypothalamic extracts has led to the conclusion that it is not a single, simple peptide, but a variety of factors which interact and synergise together [ 13], Two of these fac tors are the 41 amino acid CRF [34] and vasopressin (AVP) [11,13,28]. The many mechanisms operating in vivo to achieve the homeostasis of the hypothalamo-pituitaryadrenal axis complicate the study of CRF release.…”
mentioning
confidence: 99%
“…In conclusion, we have demonstrated a development of CRF, AVP and SRIF production by neurons over extended periods in culture as assessed by their peptide content and increasing responses to depolarizing stimuli. Such a system should prove useful in the study of the effects of environmental factors such as steroids, peptides and neurotransmitters on the maturation of peptidergic neurons and the synthesis and release of CRF, AVP and SRIF.Past work on the nature of corticotropin-releasing factor (CRF) in hypothalamic extracts has led to the conclusion that it is not a single, simple peptide, but a variety of factors which interact and synergise together [ 13], Two of these fac tors are the 41 amino acid CRF [34] and vasopressin (AVP) [11,13,28]. The many mechanisms operating in vivo to achieve the homeostasis of the hypothalamo-pituitaryadrenal axis complicate the study of CRF release.…”
mentioning
confidence: 99%
“…How¬ ever, the antibody-quenching experiments showed that immunoneutralization of AVP caused a 60% reduction in bioactivity (Fig. 2), which is indicative of synergism of VP with other factors in the CRF complex (Gillies & Lowry, 1979Gillies et al , 1984. As log dose-response lines to stalk median eminence extract, oCRF-41 and AVP are non-parallel it is incorrect to compare potencies, but the above results suggest a significant difference in the activities of extracted and released ACTH-releasing activity.…”
Section: Discussionmentioning
confidence: 96%
“…A rat 41 amino acid CRF with •One stalk median eminence (SME) extract = 3-4mg tissue homogenized lOmM-HCl containing 1 g ascorbic acid/I . tValues collected over a number of years Gillies et al , 1984present results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute organ, slice or synaptosomal preparations may suffer from cell damage, poor diffusion and the presence of sequestered neuro¬ transmitters from extrahypothalamic cell bodies. Therefore, in order to study the control of the hypothalamic corticotrophin-releasing factor (CRF) com¬ plex (Gillies, Linton & Lowry, 1982;Gillies, Puri, Linton & Lowry, 1984) we have established a system of long-term primary culture of fetal rat hypothalamic neurones (Clarke, Lowry & Gillies, 1987) coupled with the direct measurement of the released 41 amino acid-containing CRF (CRF-41) and vasopressin (AVP) by immunoassay. As with most studies, these earlier cultures were maintained in a traditional medium supplemented with serum which provides the hormones, nutrients, binding proteins and attachment factors necessary for the survival and growth of cells in vitro.…”
Section: Introductionmentioning
confidence: 99%